PERAN KELUARGA PADA DEPRESI PASCA STROKE - Mare, Agustina Chriswinda Bura; Ermalynda Sukmawati; Akub Selvia (JPK : Jurnal Penelitian Kesehatan, 2025)
Post-stroke depression (PSD) is one of the most common non-physical complications of stroke, yet it is often overlooked. The family serves as the primary support system that interacts directly with stroke survivors in daily life, thus playing a crucial role in emotional recovery and psychological adaptation after stroke. This literature review aims to explore and synthesize scientific evidence regarding the role of family support in reducing depression levels among post-stroke patients. Article searches were conducted through electronic databases: ScienceDirect and Google Scholar, covering the years 2015 to 2025. From an initial total of 1,250 articles, a rigorous screening process—consisting of title and abstract review, duplication checks, and full-text availability—yielded five articles that met all inclusion and exclusion criteria. The forms of family support identified include emotional, instrumental, and informational support. The findings indicate a significant relationship between family support and post-stroke depression, in which higher levels of family support are associated with lower levels of depression. Several factors influencing family support include the family's knowledge of stroke, caregiver burden, communication skills, and additional support from healthcare professionals. Family support contributes significantly to reducing post-stroke depression levels and should be maintained and strengthened through the active involvement of nurses and healthcare systems.